Mirette on the high wire - McCully, Emily Arnold (New York : Putnam & Grosset Group, 1997)
Mirette learns tightrope walking from Monsieur Bellini, a guest in her mother's boarding house, not knowing that he is a celebrated tightrope artist who has withdrawn from performing because of fear.
"PaperStar.".
Caldecott Medal/Honor.
Elem. School Library Collection.
Wilson's Children.
Booklist, December 2000.
Christian Library, March 1997.
Keywords: Fear -- Fiction; Tightrope walking -- Fiction; Fear -- Fiction; Tightrope walking -- Fiction